DEMOGRAPHIC CORRELATES OF RESEARCH BEHAVIOR IN HIGHER EDUCATION: AN EMPIRICAL STUDY OF TERTIARY INSTITUTIONS IN ENUGU STATE, NIGERIA - Omego, Uzoma (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Research behavior in higher education is an essential component of the contemporary education ecosystem. However, a growing indication suggests poor research behavior in Nigeria's academia. Although, the constrictions impeding efficient and globally competitive research development in the higher education system have been emphasized in the literature. However, most demographic factors are not fully explored relative to research behavior. Thus, the present paper examined research behavior based on years of service and gender. One hundred and fourteen academic staff pooled from public tertiary institutions in the Enugu States of Nigeria completed a self-report measure. The linear regression analysis conducted to determine the effect of the demographic variables on research behavior revealed that years of service F (1,112), 6.01 P<.019, and gender F (2,111), 6.01 P<.533 had no statistically significant interaction with research behavior in higher education. Notably, the R2 indicated that the predictor variables accounted for 0.81% of the observed variance in research behavior in HEI. The result has implications for research, policy-making, and the development of research behavior in higher education.